Factors Influencing Consumers’ Patronage of Unlimited Food Restaurants in The City of San Pedro, Laguna - Jocosol, Angelou Francisco (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This paper presents a narrative literature review and synthesis of a quantitative study that explored the factors influencing consumer patronage of unlimited food restaurants in San Pedro, Laguna, Philippines. The original study surveyed 400 consumers to analyze the impact of personal food attitudes and consumer expectations on their satisfaction and patronage. The review's primary purpose is to provide a deeper understanding of the findings, going beyond a simple restatement of the original data. Key findings reveal a nuanced relationship between consumer perceptions and behavior. While factors such as food quality, accessibility, and affordability were found to significantly influence consumer satisfaction, they were not the primary drivers of repeat patronage. The analysis identified service quality and ambiance as the critical differentiators, significantly influencing both satisfaction and patronage. Furthermore, personal health status emerged as a surprising and significant attitudinal factor, indicating a shift in the modern consumer's mindset even within an indulgent dining format. This paper concludes by discussing the strategic implications of these findings and proposing new avenues for future research.